The language and youth culture in kazakhstan - Gabbasov, K. N.; Shibintaeva, A. A. (ЗКАТУ им. Жангир хана, 2018)
The article is devoted to the analysis of the role of the youth of Kazakhstan in the development of language and culture. Language is perceived not only as an instrument of communication, but most importantly - as a reflection of folk culture, folk psychology and philosophy, and in many cases as the sole source of the history of the people and their spirit. The role of youth lies in the continuity of social culture, and the building of society. And also the implementation of projects in the further implementation of many social, political and cultural programs.Статья посвящена проблемам внедрения триязычия, поскольку сегодня это является важным аспектом осуществления языковой политики Республики Казахстан и считается основополагающим принципом учебного процесса. Овладение совмещенным триязычием является одной из важных и трудных задач, так как данный процесс определяет развитие функциональной грамотности, коммуникативных навыков и способности критически мыслить.
"Роль молодежи в развитии науки и инновации в ХХІ веке" в рамках программы "Рухани жаңғыру", посвящ. 20-летию столицы Республики Казахстан - города Астаны "Ел жүрегі - Астана" и 55-летию Западно-Казахстанского аграрно-технического университета имени Жангир хана: мат. третьей респ. науч.-практ. конф. студентов и магистрантов
Keywords: рк; конференции; отечественное издание; республиканская конференция; языкознание; языковая политика; полиязычие